Account classification in online social networks with LBCA and wavelets - Igawa, Rodrigo Augusto; Barbon Jr, Sylvio; Paulo, Kátia Cristina Silva; Kido, Guilherme Sakaji; Guido, Rodrigo Capobianco [UNESP]; Júnior, Mario Lemes Proença; Silva, Ivan Nunes da (Elsevier, 2016)
We developed a wavelet-based approach for account classification that detects textual dissemination by bots on an Online Social Network (OSN). Its main objective is to match account patterns with humans, cyborgs or robots, improving the existing algorithms that automatically detect frauds. With a computational cost suitable for OSNs, the proposed approach analyses the distribution of key terms. The descriptors, a wavelet-based feature vector for each user's account, work in conjunction with a new weighting scheme, called Lexicon Based Coefficient Attenuation (LBCA) and serve as inputs to one of the classifiers tested: Random Forests and Multilayer Perceptrons. Experiments were performed using a set of posts crawled during the 2014 FIFA World Cup, obtaining accuracies within the range from 94 to 100%.
Keywords: Account classification; Multilayer perceptrons; Online social networks; Random forests; Wavelets